Physical activity, physical fitness and cognitive function in adolescents - Ruivo Alves, Ana; Dias, Renata; Neiva, Henrique P.; Loureiro, Nuno; Loureiro, Vânia; Marinho, Daniel A.; Nobari, Hadi; Marques, Mário C. (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Physical activity (PA) brings cognitive, mental and physical improvements in adolescents, benefiting physical fitness (PF), cognitive results and mental health. Aim of Study. The present study aimed to analyze and characterize the level of PA, PF and attention in adolescents. Material and Methods. A descriptive cross-sectional study was performed. Forty-three adolescents aged 16 to 18 years old (16.77 ± 0.61 years), where 53.5% (n = 23) were boys participated in the study. An international questionnaire was used to accessed PA and PF levels. The CAD-S Assessment Scale revised version was used to evaluate the level of attention. Standard statistical methods were used to calculate means, standard deviations, and chi-square test. Results. The results show a moderate level of PA practice in adolescents (60.5%) and a high level of PA in boys, whom have also a good perception of their PF level 53.5% (p ≤ 0.05). In the attention capacity, high levels in the adolescents (79.1%) were observed. Conclusions. The adolescents have a good perception of their PA and PF levels, showing positive perception on cognitive function. The practice of PA daily at school and extracurricular contexts seems to be essential to obtain high levels of PF and attention, contributing to better academic performance and life quality.
Keywords: concentration; attention; school; teens; exercise